2001
DOI: 10.1091/mbc.12.8.2275
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Mechanism of Synaptogyrin Localization

Abstract: We have studied the localization of synaptogyrin family members in vivo. Both native and green fluorescent protein (GFP)-tagged Caenorhabditis elegans synaptogyrin (SNG-1) are expressed in neurons and synaptically localized. Deletion and mutational analysis with the use of GFP-tagged SNG-1 has defined a 38 amino acid sequence within the C terminus of SNG-1 and a single arginine in the cytoplasmic loop between transmembrane domain 2 and 3 that are required for SNG-1 localization. These domains may represent com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 84 publications
1
24
0
Order By: Relevance
“…This mutation lies in the cytoplasmic loop between transmembrane domains 2 and 3 of the SYNGR1 protein. Experimental evidence from Caenorhabditis elegans synaptogyrin 1, and comparative sequence analysis of rat-synaptogyrin (rat-syngr) vs ratcellugyrin (rat-cgyr) protein, suggests the importance of this cytoplasmic domain in the synaptic localization of this protein (Zhao and Nonet 2001). Hence, the Lys99-Glu mutation might affect the selective localization of SYNGR1 protein to synaptic vesicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mutation lies in the cytoplasmic loop between transmembrane domains 2 and 3 of the SYNGR1 protein. Experimental evidence from Caenorhabditis elegans synaptogyrin 1, and comparative sequence analysis of rat-synaptogyrin (rat-syngr) vs ratcellugyrin (rat-cgyr) protein, suggests the importance of this cytoplasmic domain in the synaptic localization of this protein (Zhao and Nonet 2001). Hence, the Lys99-Glu mutation might affect the selective localization of SYNGR1 protein to synaptic vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…We have also identified two common exonic variations including an ins/del polymorphism located in exon 6. According to experimental analysis on C. elegans synaptogyrin 1, this ins/del polymorphism lies within the signaling sequence for synaptic localization of synaptogyrin 1 protein (Zhao and Nonet 2001), thereby suggesting a functional consequence of this polymorphism. This ins/del polymorphism also showed association with BPAD in our case-control analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The following antibodies were used: mouse anti-RAB-3 (Nonet et al, 1997), rabbit anti-synaptotagmin (SNT-1; Nonet et al, 1993), mouse anti-SNT-1, rabbit anti-synaptobrevin (SNB-1; Nonet et al, 1998), chicken anti-synaptogyrin (SNG-1; Zhao and Nonet, 2001), rabbit anti-MEC-7 (Savage et al, 1994), mouse anti-acetylated tubulin (Sigma, St. Louis, MO;Fukushige et al, 1999), mouse anti-UNC-104 (S. P. Koushika and M. L. Nonet, unpublished data), anti-UNC-70 (Moorthy et al, 2000), rabbit anti-DYN-1 (Labrousse et al, 1998), rabbit anti-Rim (Koushika et al, 2001), mouse anti-green fluorescent protein (GFP; Clonetech, Cambridge, UK; or Roche Molecular Biochemicals, Indianapolis, IN), rabbit anti-GFP (a gift from M. Linder, Washington University), rabbit anti-UNC-64 , and rabbit anti-DHC-1 (Gonczy et al, 1999). Appropriate secondary Alexa 488 and Alexa 568 antibodies were used (Molecular Probes, Eugene, OR).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…One report on the C. elegans synaptogyrin homolog suggested that an arginine in the cytoplasmic loop was critical for targeting to nerve endings (24). An arginine is present in cellugyrin's cytoplasmic loop as well, but targeting of the protein to SLMVs was maintained despite scrambling the position of that amino acid (pHis-SCR104 -112).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies performed with rat synaptogyrin 1 and the C. elegans synaptogyrin homolog showed that the carboxyl termini of those proteins were required for reaching nerve termini in cultured hippocampal neurons and intact worms (24). Therefore, we decided to focus our initial efforts on the C terminus of cellugyrin.…”
Section: Cellugyrin Increases the Number Of Slmvs In The Cell-inmentioning
confidence: 99%